Teachers' practical experience: Improving English vocabulary of dyslexic students in regular classrooms - Rahmadhani, Putri Rizki; Emeliya Sukma Dara Damanik, (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This research explores the practical experiences of English teachers in enhancing the vocabulary acquisition of students with dyslexia in inclusive regular classrooms. The study is significant as it addresses the gap in effective vocabulary instruction for students with specific learning difficulties in mainstream settings, particularly in the Indonesian context. The objective of this research is to identify the strategies employed by teachers and the challenges they encounter when supporting dyslexic students in acquiring English vocabulary. A qualitative case study approach was used, involving two English teachers from a junior high school in Medan who had direct experience teaching students with dyslexia. Data were collected through semi-structured interviews and classroom observations. The findings reveal that teachers applied multisensory strategies, combining visual, auditory, and kinesthetic modalities, as well as scaffolded repetition and flexible learning time. These methods were effective in improving students’ vocabulary retention, engagement, and motivation. Teachers also made emotional and instructional adjustments, such as offering affirmations, reducing pressure, and allowing students to personalize their learning tools. However, the study also found that teachers faced several challenges, including a lack of training, limited access to adaptive materials, and insufficient institutional support. The implications of this research suggest the need for targeted teacher training, provision of multisensory learning resources, and stronger policy support to ensure inclusive and effective vocabulary instruction for students with dyslexia. These findings can inform educational stakeholders in improving teaching practices and policies to better serve learners with specific needs in regular classrooms.